Integrative Analysis of lncRNA-mRNA Profile Reveals Potential Predictors for SAPHO Syndrome - Sun, Yuxiu; Li, Chen; Lu, Qingyi; Jiang, Haixu; Zhu, Mengmeng; Huang, Guangrui; Wang, Ting (Frontiers in Genetics, 2021)
SAPHO syndrome is known as a rare disease characterized by inflammatory lesions on bones and skin. Polymorphism of clinical manifestation and lack of molecular biomarkers have both limited its diagnosis. Our study performed RNA sequencing (RNA-seq) and integrative bioinformatics analysis of lncRNA-mRNA profile in patients with SAPHO syndrome and healthy controls. A total of 4419 differentially expressed (DE) mRNAs and 2713 lncRNAs were identified (p < 0.05, fold change >2) and a co-expression network was constructed to further investigate their regulatory interactions. The DE lncRNAs were predicted to interact with mRNAs in both cis and trans manners. Functional prediction found that the lncRNA targeted genes may function in SAPHO syndrome by participating in biological process such as adipocytokine signaling pathway, ErbB signaling pathway, FoxO signaling pathway as well as production and function of miRNAs. The expression levels of three pairs of co-expressed lncRNA-mRNAs were validated by qRT-PCR and their relatively expression level were consistent with the RNA-seq data. The deregulated RNAs GAS7 and lnc-CLLU1.1-1:2 may serve as potential diagnostic biomarkers and the combined receiver operating characteristic (ROC) curve of the two showed more reliable diagnostic ability with an AUC value of 0.871 in distinguishing SAPHO patients from healthy controls. In conclusion, this study provides a first insight into long non-coding RNA transcriptome profile changes associated with SAPHO syndrome and inspiration for further investigation on clinical biomarkers and molecular regulators of this inadequately understood clinical entity.